Optometry in Portugal: a historical perspective - Teixeira, Eduardo (2011)
The establishment and development of optometry in Portugal resulted from the committed work of many individuals and institutions. These efforts have had good results in terms of raising the public’s awareness of the major role played by optometrists in primary eye care. Back in the late 80’s higher education in optometry was started. Ten years ago the results of scientific research on the topic first became available and are now also contributing to the success of optometry in Portugal. In regard to the optometry profession, specific regulations are to be discussed in the national parliament. The Associação de Profissionais Licenciados de Optometria (APLO), as the professional organization representing optometrists in Portugal, has been critically important in this process. This article will present an overview of the history of optometry in Portugal, of change in the foreseeable future and of the APLO’s experience and activities.